Cultural Dynamics in Couple Therapy: Enhancing Marital Intimacy Through Tailored Interventions - Atapour, Neda; darbani, seyed ali (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: This study aims to explore the effectiveness of culture-based couple therapy in improving marital intimacy among diverse couples. It seeks to address how cultural understanding and sensitivity integrated into therapeutic practices can impact marital relationships.Methods and Materials: A quasi-experimental design was employed, involving 30 couples recruited from a private counseling center and divided into experimental and control groups. The experimental group participated in an 8-week culture-based couple therapy program, focusing on cultural narratives, communication within a cultural context, conflict resolution with cultural considerations, and building a culturally inclusive relationship. Pre-test, post-test, and follow-up assessments were conducted to measure changes in marital intimacy.Findings: The results indicated significant improvements in marital intimacy scores within the experimental group compared to the control group, with sustained enhancements observed at the 3-month follow-up. Analysis of Variance with Repeated Measurements (ANOVA-RM) confirmed the positive impact of the intervention, highlighting substantial differences in marital intimacy over time and between groups.Conclusion: Culture-based couple therapy has been demonstrated to significantly enhance marital intimacy, emphasizing the importance of incorporating cultural dynamics into therapeutic interventions. This approach not only respects the cultural backgrounds of the participants but also uses these dynamics as a foundation for fostering deeper connections and understanding within couples.